Answer:
y = 3 and x = - 5
Explanation:
(a)
=
( cross- multiply )
- 8(2 + 4y) = 7(5 - 7y) ← distribute parenthesis on both sides
- 16 - 32y = 35 - 49y ( add 49y to both sides )
- 16 + 17y = 35 ( add 16 to both sides )
17y = 51 ( divide both sides by 17 )
y = 3
-----------------------------------------------
(b)
x + 7 -
=
-
![(5x)/(2)](https://img.qammunity.org/2021/formulas/mathematics/high-school/hnyjy5e30t6vqf9wjbvae27ad8bu05b1c9.png)
Multiply through by 6 to clear the fractions
6x + 42 - 16x = 17 - 15x
42 - 10x = 17 - 15x ( add 15x to both sides )
42 + 5x = 17 ( subtract 42 from both sides )
5x = - 25 ( divide both sides by 5 )
x = - 5